Hyperactive mariner transposons are created by mutations that disrupt allosterism and increase the rate of transposon end synapsis - Liu, Danxu; Chalmers, Ronald (Oxford University Press, 2014)
New applications for transposons in vertebrate genetics have spurred efforts to develop hyperactive variants. Typically, a genetic screen is used to identify several hyperactive point mutations, which are then incorporated in a single transposase gene. However, the mechanisms responsible for the increased activity are unknown. Here we show that several point mutations in the mariner transposase increase their activities by disrupting the allostery that normally serves to downregulate transposition by slowing synapsis of the transposon ends. We focused on the conserved WVPHEL amino acid motif, which forms part of the mariner transposase dimer interface. We generated almost all possible single substitutions of the W, V, E and L residues and found that the majority are hyperactive. Biochemical analysis of the mutations revealed that they disrupt signals that pass between opposite sides of the developing transpososome in response to transposon end binding. In addition to their role in allostery, the signals control the initiation of catalysis, thereby preventing non-productive double-strand breaks. Finally, we note that such breaks may explain the puzzling ‘self-inflicted wounds’ at the ends of the Mos1 transposon in Drosophila.